Insulin and extremity muscle mass in overweight and obese women - Leon, B.; Jenkins, Susan; Pepin, K.; Chaudhry, H.; Smith, K.; Zalos, G.; Miller, B.; Chen, K.; Remaley, A.; Waclawiw, M.; Sumner, A.; Cannon, R. (2013)
Background: Obesity disproportionately affects women, especially those of African descent, and is associated with increases in both fat and muscle masses. Objective: Although increased extremity muscle mass may be compensatory to fat mass load, we propose that elevated insulin levels resulting from diminished insulin sensitivity may additionally contribute to extremity muscle mass in overweight or obese women. Methods: The following measurements were performed in 197 non-diabetic women (57% black, 35% white; age 46±11 years (mean±s.d.), body mass index (BMI) range 25.0–57.7 kg m−2): dual-energy X-ray absorptiometry for fat and extremity muscle masses; exercise performance by duration and peak oxygen consumption (VO2 peak) during graded treadmill exercise; fasting insulin and, in 183 subjects, insulin sensitivity index (SI) calculated from the minimal model. Results: SI (range 0.5–14.1 l mU−1 min−1) was negatively, and fasting insulin (range 1.9–35.6 μU ml−1) positively associated with extremity muscle mass (both P<0.001), independent of age and height. Sixty-seven percent of women completed 6 months of participation in a weight loss and exercise program: we found a significant association between reduction in fasting insulin and a decrease in extremity muscle mass (P=0.038), independent of reduction in fat mass or improvement in exercise performance by VO2 peak and exercise duration, and without association with change in SI or interaction by race. Conclusions: Hyperinsulinemia in overweight or obese women is associated with increased extremity muscle mass, which is partially reversible with reduction in fasting insulin concentration, consistent with the stimulatory effects of insulin on skeletal muscle.